Sustainable supply chains : A research-based textbook on operations and strategy - Bouchery, Yann; Corbett, Charles J.; Fransoo, Jan C.; Tan, Tarkan (Springer series in supply chain management, 2017)
Contents: Measuring environmental impacts in supply chains; Operational aspects of sustainable supply chains; Business models and strategy in sustainable supply chains; The social dimension of sustainable supply chains.